Contemporary Management of Metastatic Gastrointestinal Stromal Tumors: Systemic and Locoregional Approaches. Issue 1 (June 2016) - Ang, Celina; Maki, Robert
Abstract The treatment of metastatic gastrointestinal stromal tumors (GISTs) changed dramatically with the introduction of imatinib into the therapeutic lexicon in 2001. Over the past 15 years, tyrosine kinase inhibitors in the adjuvant and metastatic settings have remained the standard of care for this disease, though alternate classes of agents and new therapeutic targets are being actively explored in clinical trials. Although data are limited, the use of surgical and non-surgical locoregional techniques for the treatment of GIST metastases has increased and given reports of promising and durable responses. Herein we provide an overview of the contemporary therapeutic landscape of metastatic GIST.